Do disease-modifying antirheumatic drugs and non-steroidal anti-inflammatory drugs increase the burden on ankylosing spondylitis patients with mild-moderate COVID-19? evidence from a retrospective cohort study - Li, Yan; Hu, Zhengyuan; Guo, Yufei; Zhao, Zheng; Li, Kunpeng; Wang, Xiuru; Zhang, Jie; Liang, Dongfeng; Zhang, Jianglin; Hu, Xiaoyue; Zhu, Jian; Huang, Feng (Frontiers in Pharmacology, 2023)
Objectives: The impact of non-steroidal anti-inflammatory drugs (NSAIDs), conventional synthetic disease-modifying antirheumatic drugs (csDMARDs) and tumor necrosis factor inhibitors (TNFi) on the outcomes of mild-moderate COVID-19 in patients with ankylosing spondylitis (AS) remains unclear. This study aimed to evaluate the effects of NSAIDs, csDMARDs and TNFi on AS patients with mild-moderate COVID-19. Methods: This cohort study utilized patient-reported PCR/antigen tests to determine the occurrence of COVID-19 and assessed clinical manifestations to determine its severity. The study focused on two primary outcomes: an increased number of COVID-19 symptoms and a prolonged disease course (longer than 10 or 28 days). Modified Poisson regression was performed to analyze the association between exposures and outcomes. Results: A total of 521 patients were included in the analysis. The median age was 34.8 (inter-quartile range: 27.2-46.7), with 420 (80.6%) being male. Among the patients, 52 (10.0%) had comorbidities and 443 (85%) had been vaccinated. After adjusting for confounding factors, there was no significant association between csDMARDs or TNFi and the presence of more than 5 symptoms in mild-moderate COVID-19 (adjusted relative risk (RRa) 1.08, 95% CI: 0.84-1.40 or 1.09, 0.92-1.29 for csDMARDs or TNFi, respectively), whereas the prevalence of experiencing more than 5 symptoms increased in patients with NSAIDs monotherapy (RRa 1.22, 95% CI: 1.01-1.46). Similarly, there was no significant association with having more than 10 symptoms (RRa 0.65, 95% CI: 0.26-1.64; 0.95, 0.36-2.54; and 1.01, 0.53-1.91 for NSAIDs, csDMARDs, and TNFi, respectively). Patients who had pre-existing use of NSAIDs, csDMARDs and TNFi had similar odds of experiencing a disease course longer than 10 days (RRa 1.17, 95% CI: 0.82-1.66; 1.18, 0.78-1.77; and 1.22, 0.92-1.63 for NSAIDs, csDMARDs, and TNFi, respectively) and longer than 28 days (RRa 0.94, 95% CI: 0.31-2.81; 0.97, 0.25-3.74 and 1.05, 0.44-2.49, respectively) compared to those not using medication. Conclusion: AS patients treated with csDMARDs or TNFi did not show inferior outcomes in terms of symptom burden or recovery compared to those not using medication in mild-moderate COVID-19. The observed inverse association between pre-existing NSAIDs use and COVID-19 symptom burden in AS deserves further investigations.